PENGARUH PENGGUNAAN METODE PERSONALIZED SYSTEM OF INSTRUCTION (PSI) TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Aripin Nurmantoro, Muh (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2017)
The purpose of this study are to find out students? math learning achievement description using Personalized System of Instruction (PSI) method, to find out students? math learning achievement description using expository method and  to find out there?s influence using Personalized System of Instruction (PSI) method toward students? math learning achievement. The population is all students of grade X SMA Negeri I Sliyeg. Furthermore the sample is taken 2 of 8 grades? by simple random sampling technique. Grade X-3 as first experiment class that use Personalized System of Instruction (PSI) method and grade X-2 as second experiment class that use expository method. The instrument of this research applied six essays and each indicator represents one point essay and the validity and reliability of the instrument has been examined. Based on the analysis result of the postest, know that is a difference between students? learning achievement using Personalized System of Instruction (PSI) method and expository method. As a result, in can be concluded that the influence Personalized System of Instruction (PSI) method toward students? math learning achievement.